2020
DOI: 10.3389/fpsyt.2020.00134
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of the “Work–Family Conflict” With Occupational Stress—A Cross-Sectional Study Among University Employees

Abstract: Background: The working conditions at universities and hospitals are reported to be stressful. Several national and international studies have investigated occupational stress in hospitals. However, scientific studies at colleges and universities addressing psycho-social stress factors and their potential consequences are scarce. In this context, the consequences and correlations of the factor of work-family conflict, in particular, are currently uninvestigated. The aim of our study was to assess data on psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
3
22
0
1
Order By: Relevance
“…Previous studies have shown that work stress is related to one's demographic characteristics, 13,17 and that child care at home is a common problem for hospital staff, 28,29 which is an important factor leading to work‐family conflicts 30 . The present results showed that hospital staff with minor children was more stressed, confirming the viewpoint presented in prior research.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that work stress is related to one's demographic characteristics, 13,17 and that child care at home is a common problem for hospital staff, 28,29 which is an important factor leading to work‐family conflicts 30 . The present results showed that hospital staff with minor children was more stressed, confirming the viewpoint presented in prior research.…”
Section: Discussionsupporting
confidence: 90%
“…We confirm hypothesis 1, that postulated that work-family conflict influences burnout levels, adding one more piece of evidence to the vast existing literature (Jerg-Bretzke et al 2020;Medrano & Trógolo, 2018;Smith et al, 2018;Terry & Woo, 2020). Nonetheless, as expected, we find some gender differences.…”
Section: Discussionsupporting
confidence: 89%
“…Work and family are the most important facets in both women's and men's lives and conflictive demands arising from them have turned out to be one of the most relevant psycho-social risks in today's occupational world. Work-family conflict has serious consequences for employees and it is related to stress (Tziner & Sharoni, 2014), psychological health (Nigatu & Wang, 2018;Sun at al., 2020), and burnout (Jerg-Bretzke et al, 2020;Medrano & Trógolo, 2018;Smith et al, 2018;Terry & Woo, 2020), including its dimensions: emotional exhaustion and depersonalisation (Wang et al, 2012). Such outcomes of work-family conflicts, like burnout, could, for its part, develop into significant problems for employees and organizations (Palenzuela et al, 2019).…”
Section: Palabras Clavementioning
confidence: 99%
“…For example, Frone et al [ 17 ] found FWC was longitudinally related to poor physical health and more depressive symptoms, while WFC was longitudinally related to more heavy alcohol consumption. While other studies found WFC and FWC had similar effects on mental and somatic health [ 18 ]. On the whole, both types of conflict go against to employees’ mental health but sometimes with difference in the magnitude of adverse effect.…”
Section: Introductionmentioning
confidence: 93%